Diagnostic utility of amylase α-1A, MOC 31, and CD 82 in renal oncocytoma versus chromophobe renal cell carcinoma - Nehal S Abouhashem; Eman H Abdelbary; Mohamed M H. Abdalla; Mohamed El-Shazly (Indian Journal of Pathology and Microbiology, 2020)
Objective: Renal oncocytoma (RO) and chromophobe renal cell carcinoma (ChRCC) originate from the same cell origin, that is, the intercalated cells of the collecting duct.[1] In most cases, there are clear morphologic differences between RO and ChRCC; however, in some instances, overlapping features may be encountered and the differentiation between the two entities becomes difficult.[2] Several immunohistochemical markers with different expression patterns in ChRCC and RO have been described to rule out this dilemma. Materials and Methods: About 47 primary renal neoplasms that had been diagnosed as RO or ChRCC were submitted for immunohistochemical staining of amylase α-1A (AMY1A), MOC 31, and CD 82. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy have been analyzed. Results: AMY1A positivity was observed in all RO cases in our work with 91.7% sensitivity and 100% specificity in the diagnosis of RO. The PPV of its expression was (100%) and NPV (97.2%) with a diagnostic accuracy of 97.9%. A significant high expression of MOC 31 was observed in ChRCC compared to its expression in RO with a statistical significance (P < 0.001). In addition, we obtained 82.9% sensitivity and 91.7% specificity of MOC 31 expression in the diagnosis of ChRCC. The positive predictive value (PPV) was (96.7%), negative predictive value (NPV) (64.7%) with diagnostic accuracy (85.1%). In our studied cases, we detected positive immunoexpression of CD 82 in 10 cases (83.3%) of ChRCC. However, it was lost in all RO cases (100%). CD 82 sensitivity and specificity in differentiating ChRCC from RO were 100% and 83.3%, respectively. Conclusion: We propose MOC 31 and CD 82 as negative immunostains for RO, as these markers are commonly expressed in ChRCC. In conjunction with AMY1A strong immunopositivity in RO cases, we provide a triple panel of biomarkers (AMY1A, MOC 31, and CD 82) for the distinction between RO and ChRCC.